Postreproductive lifespans are rare in mammals. Issue 5 (31st January 2018) - Ellis, Samuel; Franks, Daniel W.; Nattrass, Stuart; Cant, Michael A.; Bradley, Destiny L.; Giles, Deborah; Balcomb, Kenneth C.; Croft, Darren P.
Abstract: A species has a post‐reproductive stage if, like humans, a female entering the adult population can expect to live a substantial proportion of their life after their last reproductive event. However, it is conceptually and statistically challenging to distinguish these true post‐reproductive stages from the usual processes of senescence, which can result in females occasionally surviving past their last reproductive event. Hence, despite considerable interest, the taxonomic prevalence of post‐reproductive stages remains unclear and debated. In this study we use life tables constructed from published data on wild populations of mammals, and statistical measures of post‐reproductive lifespans, to distinguish true post‐reproductive stages from artefacts of senescence and demography in 52 species. We find post‐reproductive stages are rare in mammals and are limited to humans and a few species of toothed whales. By resolving this long‐standing debate, we hope to provide clarity for researchers in the field of evolutionary biology and a solid foundation for further studies investigating the evolution and adaptive significance of this unusual life history trait. Abstract : Despite considerable interest, the taxonomic prevalence of extended human menopause‐like postreproductive stages in mammals remains unclear and debated. In this article, we show that postreproductive lifespans are limited to humans and a couple of species of toothed whale.